Pengaruh Literasi Keuangan, Lifestyle Hedonis, Dan Sikap Keuangan Pribadi Terhadap Perilaku Keuangan Mahasiswa (Studi Pada Mahasiswa Program Studi Manajemen Universitas Islam Malang Angkatan 2020) - Kumaidah, Siti; Basalamah, Muhammad Ridwan; Arsyianto, Muhammad Tody (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract The advancement of globalization and digitalization has changed the financial behavior of students. Their interest in a trend makes the amount of their spending uncontrollable and makes them make inappropriate financial decisions. Thus, an understanding of good financial management is needed. The purpose of this study was to determine the effect of financial behavior, hedonic lifestyle, and personal financial attitudes on the financial behavior of students of the management study program at the Islamic University of Malang in 2020. The number of samples in this study was 83 respondents who were taken using the Slovin formula. Data analysis methods using multiple linear regression analysis as well as classical assumption tests and hypothesis testing and using the SPSS analysis tool program. The results of this study indicate that Financial Literacy, Hedonic Lifestyle, and Personal Financial Attitudes simultaneously have a positive and significant effect on Financial Behavior. Financial Literacy partially has a significant positive effect on Financial Behavior. A hedonic Lifestyle partially has a significant positive effect on Financial Behavior. Personal Financial Attitudes have no significant effect on Financial Behavior. Keywords: Financial Literacy, Hedonic Lifestyle, Personal Financial Attitude, Financial Behavior